DETERMINATION OF TRACEABLE GENOTOXIC IMPURITY CHLOROACETYL CHLORIDE A CARCINOGEN BY LC/MS/MS IN DRUG SUBSTANCES - S, Natarajan; Bk, Kempegowda; M, Bharathiar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: A simple liquid chromatography-mass spectroscopy/mass spectroscopy (LC/MS/MS) method was developed for determining chloroacetyl chloride (CAC), which is possible genotoxic impurity at trace levels in pharmaceutical drug substances. Methods: The suitable LC/MS/MS compatible buffers acetonitrile and ammonium format were used to avoid matrix interferences and for better detectability. This method eliminates the solvent extraction and derivatization steps and requires only the direct injection of the sample into the LC/MS. Results: The method is specific, accurate, and critical validation parameters have been done and established the limit of quantitation level of 0.003 Âµg/g. Conclusion: The method possesses the lowest detection level when compared with other methods referred in this journal. Keywords: Liquid chromatography-mass spectroscopy, Chloroacetyl chloride, Active pharmaceutical ingredients, Carcinogenic, Drug substance.